I'm having trouble understanding how to reduce lambda terms to normal form. We just got assigned a sheet with a few problems to reduce, and the only helpful thing I've found is the following example in the book:
->(λx.(λy.y+1)((λy.y+1)x))2 //How'd it get to this??
I'm pretty sure I understand most of it... except for their first step (everything else is pretty much substitution as if it was: f(x) = x + 3, x = y, therefore y+3)
Can someone please explain this to me? I pretty much have no experience with lambda calculus.